Mastering machine learning on AWS advanced machine learning in Python using SageMaker, Apache Spark, and TensorFlow - Mengle, Saket S. R. (Packt Publishing, Limited, 2019)
This book will help you master your skills in various artificial intelligence and machine learning services available on AWS. Through practical hands-on examples, you'll learn how to use these services to generate impressive results. You will have a tremendous understanding of how to use a wide range of AWS services in your own organization.